BUDAYA ORGANISASI MASYARAKAT DESA WERDHI AGUNG KECAMATAN DUMOGA TENGAH KABUPATEN BOLAANG MONGONDOW - MAMAHIT, JEKLIN; LENGKONG, FLORENCE DAICY; TULUSAN, FEMMY (Sam Ratulangi University, 2019)
The cultural life of the Werdhi Agung Village Community Organization is strongly influenced or adheres to their beliefs, namely Darma Hinduism which is the community of Werdhi Agung Village since a few centuries ago, therefore the life and culture of the Werdhi Agung Village community organization cannot be separated from the teachings of the Hindu Darma. the community of Werdhi Agung Village can be seen through how the community carries out family relations between people. The Werdhi Agung community is so obedient in keeping in mind where they come from, the Werdhi Agung people from the Balinese tribe are people who are bound by an awareness of the unity of their organizational culture. The awareness is reinforced by the common language of the Werdhi Agung Village community, despite this awareness but Werdhi Agung Village organizational culture embodies many variations of life in the community. The Hindu Darma religion which has long been embraced by the community as a foundation of public trust that has long been integrated into the community of Werdhi Agung Village, is also felt as one of the elements that strengthens the culture of its community organization. The Banjar Organizational Culture in Werdhi Agung Village is an organization of one social unit based on regional unity, the unity is strengthened by the unity of customs and diversity ceremonies carried out by the people of Werdhi Agung Village. The nature of the membership of the Banjar Organization Culture is only limited to people born in the Banjar region. The culture of the Werdhi Agung Village community organization has high moral values because organizational culture is a tradition and inheritance given by the old people of the Werdhi Agung Village community long ago. Organizational culture is very important for the people of Werdhi Agung Village because village community organizations can help each other among people and every organization in Werhdi Agung Village can not be separated from the direction given by the religion in the hope that there is a unified organizational culture among the community. safe and comfortable, a sense of belonging to each other and a sense of kinship among the people of Werdhi Agung Village.Keywords: Culture, Organizational, Society.